La realidad : un modo de dialogar con las particularidades de los estudiantes de los grados primero B y segundo del Colegio Alfred Binet (2021)
Quality education in equal opportunities from learning, culture and society becomes an important factor when thinking about teaching-learning strategies and how teachers react with respect to all the realities that surround to each of the boys and girls. Contact with reality is essential to assertively attend to the diversity of learning, since doing so allows the training activity to be one for everyone. The purpose of this investigative exercise is, firstly, to broaden the concept of diversity so that, based on the needs, interests and concerns of boys and girls, a greater participation, appropriation of the contents in the learning processes, and to make teachers more aware of the importance of teaching processes in the particular life of each of the students present in the classroom. The research is carried out from a qualitative methodology with an ethnographic approach and the results showed, among other things, that understanding diversity, allows us to create bridges in which what is seen in the classroom can be applied to daily life.